Taxonomy of Person-Descriptive Terms in Polish: A Psycho-Lexical Study - Gorbaniuk, Oleg; Czarnecka, Ewelina; Chmurzyńska, Marta (Current Problems of Psychiatry, 2011)
This paper describes the development of a comprehensive taxonomy of person-descriptive terms in Polish, organized in two studies. In the first study, two judges searched through The Universal Dictionary of Polish Language (100 000 terms) for person-descriptive terms. In the second study, 4555 person-descriptive adjectives were classified by nine judges into 13 different subcategories of the psycho-lexical classification system. Our studies provide comprehensive and representative lists of Polish adjectives for describing personality traits, which may be used in establishing the structure of human personality descriptions by means of self-rating or peerrating surveys of a full age range Polish population of respondents.